Silent Atrial Fibrillation in Elderly Pacemaker Users: A Randomized Trial Using Home Monitoring. Issue 3 (28th September 2015) - Lima, CEB; Martinelli, M; Peixoto, GL; Siqueira, SF; Wajngarten, Maurício; Silva, Rodrigo Tavares; Costa, Roberto; Filho, Roberto; Ramires, José Antônio Franchini
Abstract : Background: Pacemaker with remote monitoring (PRM) may be useful for silent atrial fibrillation (AF) detection. The aims of this study were to evaluate the incidence of silent AF, the role of PRM, and to determine predictors of silent AF occurrence. Methods: Three hundred elderly patients with permanent pacemaker (PPM) were randomly assigned to the remote group (RG) or control group (CG). All patients received PPM with remote monitoring capabilities. Primary end point was AF occurrence rate and the secondary end points were time to AF detection and number of days with AF. Results: During the average follow‐up of 15.7±7.7 months, AF episodes were detected in 21.6% (RG = 24% vs CG = 19.3%, P = 0.36]. There was no difference in the time to detect the first AF episode. However, the median time to detect AF recurrence in the RG was lower than that in the CG (54 days vs 100 days, P = 0.004). The average number of days with AF was 16.0 and 51.2 in the RG and CG, respectively (P = 0.028). Predictors of silent AF were left atrial diameter (odds ratio [OR] 1.2; 95% CI = 1.1–1.3; P < 0.001) and diastolic dysfunction (OR 4.8; 95% CI = 1.6–14.0; P = 0.005). Conclusions: The incidence of silent AF is high in elderly patients with pacemaker; left atrial diameter and diastolic dysfunction were predictors of its occurrence. AF monitoring by means of pacemaker is a valuable tool for silent AF detection and continuous remote monitoring allows early AF recurrence detection and reduces the number of days with AF.